Stratified Model Of The Internet Of Things Infrastructure - Jamil Alsayaydeh, Jamil Abedalrahim; Shkarupylo, Vadym; Hamid, Mohd Saad; Skrupsky, Stepan; Oliinyk, Andrii (Medwell Journals, 2018)
The scale and the complexity of modern network solutions built upon the promising and popular paradigm of the Internet of Things brings to the table the vital need for novel approaches to these solutions designing.To foster the further developments in this direction,the stratified model of the Internet of Things infrastructure has been proposed.There are distinguished three hierarchical layers:the lowest one is represented with web services, the intermediate one-with usage scenarios,the upper layer-with applicability domain of the Internet of Things solution.The model is based on the Temporal Logic of Actions and corresponding TLA+ formalism.To check the specification,created with respect to the proposed model, the TLC model checker has been used.Two approaches to automated TLC-verification have been utilized-model checking by way of breadth-first search and by way of depth-first search.The smart home scenario has been considered.